2015
DOI: 10.1111/jvim.13654
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Deficits Including Auditory Loss and Recovery of Function in Horses with Temporohyoid Osteoarthropathy

Abstract: BackgroundAuditory loss is a common deficit in horses with temporohyoid osteoarthropathy (THO), however, recovery of function is unknown.Hypothesis/ObjectivesTo investigate neurologic function with emphasis in audition in horses with THO after treatment. To describe anatomical alterations of the petrous temporal bone that might result in auditory loss.AnimalsTwenty‐four horses with a clinical diagnosis of THO.MethodsProspective study. A brainstem auditory evoked response (BAER) study was done as part of the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 22 publications
(120 reference statements)
0
17
1
Order By: Relevance
“…Common clinical signs of THO include facial and/or vestibulocochlear nerve dysfunction and head tossing. Less common signs include dysphagia and seizure-like activity [4,5,[7][8][9][10][11]. Some of the common behavioural signs associated with THO are head shaking, ear rubbing and bit avoidance [4,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common clinical signs of THO include facial and/or vestibulocochlear nerve dysfunction and head tossing. Less common signs include dysphagia and seizure-like activity [4,5,[7][8][9][10][11]. Some of the common behavioural signs associated with THO are head shaking, ear rubbing and bit avoidance [4,9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Less common signs include dysphagia and seizure-like activity [4,5,[7][8][9][10][11]. Some of the common behavioural signs associated with THO are head shaking, ear rubbing and bit avoidance [4,9,12]. Diagnosis is based on a combination of clinical signs and diagnostic imaging, including guttural pouch endoscopy, skull radiography and/or computed tomography (CT) [4,8,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Auditory loss is common in horses with temporohyoid osteoarthropathy (THO); however, recovery of function is unknown. In this study Monica Aleman and colleagues in the USA investigated neurological function with emphasis on audition in horses with THO after treatment and reported anatomical alterations of the petrous temporal bone that might result in auditory loss .…”
Section: Auditory Loss In Horses With Temporohyoid Osteoarthropathymentioning
confidence: 99%
“…However, antemortem diagnosis of temporal bone fractures was uncommon prior to the advent of CT, as these fractures are often not radiographically apparent. Previous studies have reported temporal bone fractures using CT in 25% (4/16) to 36% (4/11) of horses with temporohyoid osteoarthropathy, however, these reports did not include detailed descriptions of the fracture configurations. Bacterial meningitis, seizures, and death have been reported as sequelae of these temporohyoid osteoarthropathy‐associated temporal bone fractures .…”
Section: Introductionmentioning
confidence: 99%
“…Temporohyoid osteoarthropathy is a disorder characterized by progressive osseous proliferation surrounding and eventually bridging the temporohyoid joint. Temporohyoid osteoarthropathy leads to a variety of clinical presentations ranging from behavior changes (head shaking, resistance to the bit, and ear rubbing) to severe neurologic dysfunction mainly referable to the facial and vestibulocochlear nerves …”
Section: Introductionmentioning
confidence: 99%